Association between the OXTR rs53576 genotype and latent profiles of post-traumatic stress disorder and depression symptoms in a representative sample of earthquake survivors. Issue 2 (3rd March 2020) - Cao, Chengqi; Wang, Li; Wu, Jianhui; Li, Gen; Fang, Ruojiao; Liu, Ping; Luo, Shu; Elhai, Jon D.
ABSTRACT: Background and Objectives: Post-traumatic stress disorder (PTSD) and major depressive disorder are commonly experienced mental disorders among psychological trauma victims. Few studies have investigated the genetic basis for population heterogeneity of trauma-related psychopathology, including PTSD and depression. This study examined the main and interaction effects of the OXTR rs53576 genotype in distinguishing four subgroups identified by symptom profiles of PTSD and depression symptoms using latent proﬁle analysis. Design: A cross-sectional design with a gene-environment interaction approach was adopted in the current study. Methods: This study was a secondary data analysis conducted on a sample of 1196 adult earthquake survivors. Participants completed assessments of earthquake exposure, PTSD symptoms, and depression symptoms. The rs53576 polymorphism of OXTR was genotyped using a custom-by-design 2×48-Plex SNPscan TM Kit. Results: Multinomial logistic regression analyses revealed the main effects of the rs53576 genotype on symptom profiles. Specifically, G allele carriers were more likely in the combined PTSD-depression group than in the low symptom, predominantly depression, and predominantly PTSD groups. No significant interaction effects between this genotype and earthquake exposure on symptom profiles were found. Conclusions: Our findings support a genetic basis for trauma-related psychopathology heterogeneity. Furthermore, results provide preliminary evidence for the role of OXTR in PTSD/depression comorbidity.